The Management of Gastroenteropancreatic Neuroendocrine Tumors with Somatostatin Analogues - Khagi, Simon; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Gastroenteropancreatic neuroendocrine tumors are a heterogeneous group of malignancies, characterized by varying degrees of biological activity and metastatic potential. A common thread between this wide mix of neoplasms has remained their sensitivity to hormonal modulation with somatostatin analogues. New analogues of somatostatin have been recently introduced and are beginning to shape a different picture of how we treat and monitor for response in patients with gastroenteropancreatic neuroendocrine tumors. Here we discuss three important abstracts presented at the annual meeting of the American Society for Clinical Oncology (ASCO) 2014 (#4107, #4108, and #4111) that highlight the changing landscape of somatostatin-based therapy. Image: Pasireotide